California Stress, Trauma, and Resilience Study (CalSTARS) protocol: A multiomics-based cross-sectional investigation and randomized controlled trial to elucidate the biology of ACEs and test a precision intervention for reducing stress and enhancing resilience - Lauren Y. Kim; Sophia Miryam Schüssler-Fiorenza Rose; Summer Mengelkoch; Daniel P. Moriarity; Jeffrey Gassen; Jenna C. Alley; Lydia G. Roos; Tao Jiang; Arash Alavi; Durga Devi Thota; Xinyue Zhang; Dalia Perelman; et al. (Stress)
Adverse Childhood Experiences (ACEs) are very common and presently implicated in 9 out of 10 leading causes of death in the United States. Despite this fact, our mechanistic understanding of how ACEs impact health is limited. Moreover, interventions for reducing stress presently use a one-size-fits-all approach that involves no treatment tailoring or precision. To address these issues, we developed a combined cross-sectional study and randomized controlled trial, called the California Stress, Trauma, and Resilience Study (CalSTARS), to (a) characterize how ACEs influence multisystem biological functioning in adults with all levels of ACE burden and current perceived stress, using multiomics and other complementary approaches, and (b) test the efficacy of our new California Precision Intervention for Stress and Resilience (PRECISE) in adults with elevated perceived stress levels who have experienced the full range of ACEs. The primary trial outcome is perceived stress, and the secondary outcomes span a variety of psychological, emotional, biological, and behavioral variables, as assessed using self-report measures, wearable technologies, and extensive biospecimens (i.e. DNA, saliva, blood, urine, & stool) that will be subjected to genomic, transcriptomic, proteomic, metabolomic, lipidomic, immunomic, and metagenomic/microbiome analysis. In this protocol paper, we describe the scientific gaps motivating this study as well as the sample, study design, procedures, measures, and planned analyses. Ultimately, our goal is to leverage the power of cutting-edge tools from psychology, multiomics, precision medicine, and translational bioinformatics to identify social, molecular, and immunological processes that can be targeted to reduce stress-related disease risk and enhance biopsychosocial resilience in individuals and communities worldwide.